Challenges of intra-institutional transfer of care from paediatric to adult congenital cardiology: the need for retention as well as transition. (13th April 2015) - Bohun, Claudine M.; Woods, Patricia; Winter, Christiane; Mitchell, Julie; McLarry, Joel; Weiss, Joseph; Broberg, Craig S.
Abstract: Background: Transferring patients with CHD from paediatric to adult care has been challenging, especially across institutions. Within a single institution, some issues such as provider interaction, information exchange, or administrative directives should not play a significant role, and should favour successful transfer. Objective: We studied patients who were eligible for transfer to the adult congenital heart disease service within our institution in order to identify factors associated with successful transfer to adult care providers versus failure to transfer. Methods: Patients above18 years of age with CHD who were seen by paediatric cardiologists before January, 2008 were identified through a patient-care database. Records were reviewed to determine follow-up between 2008 and 2011 and to determine whether the patient was seen in the adult congenital cardiology clinic, paediatric cardiology clinic, or had no follow-up, and statistical comparisons were made between groups. Results: After reviewing 916 records, 229 patients were considered eligible for transition to adult congenital cardiology. Of these, 77 (34%) were transferred successfully to adult congenital cardiology, 47 (21%) continued to be seen by paediatric cardiologists, and 105 (46%) were lost to follow-up. Those who transferred successfully differed with regard to complexity of diagnosis, insurance, and whether a formal referral was made by a paediatric care provider. Only a small fraction of the patients who were lost to follow-up could be contacted. Conclusion: Within a single institution, with shared information systems, administrations, and care providers, successful transfer from paediatric to adult congenital cardiology was still poor. Efforts for successful retention are just as vital as those for transfer.